Development of Nature Detox Android Based Mobile Application - Lew, Ee Vin; Murli, Norhanifah (Applied Information Technology And Computer Science, 2021)
Physical health is very important for each and every one of us. However, most of us reluctant to figure out their daily routine, food intake and physical fitness routine. People tend to opt for fast food instead of eating clean because it saves time and sold at the most affordable price. An unhealthy diet coupled with none physical fitness routine are a root cause of all the diseases. The government has emphasized all of us to live healthily and boost our immune system due to the pandemic of Coronavirus (Covid-19). The major contributing factors to obesity among Malaysians include unhealthy and uncontrolled food intake, lack of physical activity and genetics. If we scroll Google Play Store and choose a health application, most of the application creator only provide all types of workouts with either eat clean or water drinking. To raise health awareness, a Nature Detox Mobile Application using an android platform has been created. It is an application that intends to raise health awareness for user who aged between 18 to 40 years old on how to keep themselves healthy by eating clean food, drinking juices and exercising. The objectives of the application is developed in mobile-based Android Platform. The methodology used to develop the application is AGILE model. Testing had been carried out and the application has received a positive feedback from the target user with 92% overall percentage based on the system usability scale. The application can operate smoothly and achieve all of the objectives. Finally, it is anticipated that this project would assist the user in their daily lives.